Kesadaran Berkonstitusi bagi Penegak Hukum terhadap Putusan Mahkamah Konstitusi sebagai Upaya Menjaga Kewibawaan Peradilan - Ahmad Yani (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
The decision of the Constitutional Court is a type of decision that is declaratoir constitutive. When the decision of the Constitutional Court states that the law is not binding, because it is contrary to the Constitution, then by itself the decision also creates a new legal situation. The formulation of the problem that will be answered in this research is how the concept of building constitutional awareness for law enforcement institutions to obey the decisions of the Constitutional Court. This research is a type of juridical-normative research, to conduct a search on the decisions of the Constitutional Court. Disobedience to the decision of the Constitutional Court will have fatal consequences, from the potential for a reduction in the function of the Constitutional Court institution to the occurrence of constitutional justice delays. Obedience to the decisions of the Constitutional Court cannot only rely on the legal awareness of the community and state institutions, but also needs to be supported by “coercive” instruments. Therefore, the importance of collaborative collaboration across state institutions so that the decisions of the Constitutional Court can be implemented properly as they should. In addition, it is necessary to design the imposition of sanctions for acts of disobedience to the decisions of the Constitutional Court.